THE ENVY AS THE CAUSE OF THE WEAKENING OF THE SOCIAL CAPITAL IN THE COMMUNAL COMMUNITY - Helena Anggraeni Tjondro Sugianto (Department of Management - Institut Shanti Bhuana, 2020)
This research aims to find the cause of the weakening of social capital in a communal community. The study was conducted using qualitative methods in a village where people lived communally for generations. The findings of this study are that it turns out that communal life that has lasted from generation to generation makes people live in a strong brotherhood with an egalitarian spirit. However, at this time when more and more modern times occur people are experiencing cultural shock because they are not ready to see their neighbors more prosperous than they are. This causes jealousy because they previously lived with the same level of welfare. As a result, the social capital potential due to strong brotherhood has not developed. During this time the weakening of social capital is usually associated with the formal institutions that play a role in it. However, this article found that jealousy can also weaken social capital in a society.